Elevated uric acid to serum albumin ratio: a predictor of short-term outcomes in Chinese heart failure patients - Xianling Liu; Aihui Chu; Xiahao Ding (Frontiers in Nutrition)
BackgroundThe prognostic value of the uric acid to albumin ratio (UAR) in heart failure (HF) remains underexplored. The objective of this research was to investigate the link between UAR and short-term outcomes in Chinese HF patients.MethodsWe analyzed data from 1893 HF patients, out of an initial cohort of 2008, who had available UAR measurements. The skewed distribution of UAR data was addressed by applying a Log-10 (lg) transformation and stratifying patients into three groups accordingly (low to high). The final outcome was identified as mortality or hospital readmission within 28 days. We employed restricted cubic spline analysis (RCS), Kaplan–Meier survival curves, and Cox proportional hazards models to evaluate the link between UAR and short-term outcomes.ResultsAmong 1893 patients with HF [≥ 70 years, 1,382 (73.0%); female, 1,100 (58.1%)], the incidence of 28-day outcome was 8.6%. The RCS analysis suggested a positive relationship between lg(UAR) and 28-day outcomes, with no evidence of nonlinearity (p = 0.008). The cumulative incidence of 28-day readmission/death indicated that patients in the tertile 3 faced a significantly elevated risk of adverse outcomes (p < 0.001). Cox proportional hazards models showed that an elevated UAR was associated with a greater likelihood of 28-day mortality or hospital readmission (HR = 2.433, 95% CI: 1.638–3.615, p < 0.001). Even after accounting for possible confounding variables, the result still existed (HR = 1.594, 95% CI: 1.032–2.462, p = 0.036). Moreover, the associations were consistent in various subgroups, and sensitivity analysis (all p > 0.05).ConclusionIncreased UAR correlates with a heightened risk of short-term death or hospital readmission in Chinese individuals suffering from HF. Maintaining a relatively lower UAR could potentially improve the clinical prognosis for these patients.